Investigating the Effect of Cultural Diversity Management and Employee Engagement on Work Performances: Mediating Role of Cross-Cultural Leadership - Marpaung, Sonia Margaretha; Nasution, Harmein; Siahaan, Elisabeth (Indonesia Academia Research Society, 2023)
Sampoerna Academy Medan is one of the international schools that contributes to the number of foreign workers (expatriates). Cultural diversity at Sampoerna Academy Medan becomes an opportunity and challenge for this organization to achieve optimal employee performance. This study has identified and classified three large categories, namely a mismatch in cultural diversity management leading to a high level of staff and leader turnover, employee disengagement in optimizing their performance, and the phenomenon of self-adjustment to changes in leaders in three consecutive years. This study uses the transformational leadership theory, cross-cultural leadership styles, cultural diversity management, and employee engagement concepts. This study applies triangulation through in-depth interviews, observation, and with employees at Sampoerna Academy Medan. By using qualitative methods and involving 12 respondents consisting of one local manager, one Filipino manager, one Indian manager, two local staff, two Indian staff, 2 Philippine staff, 1 Malaysian staff, 1 Chinese staff, and 1 England staff. The study found several short-term and long-term recommendations that can support performance optimization at Sampoerna Academy Medan, Indonesia.